The effects of allergen-specific immunotherapy on polymorphonuclear leukocyte functions in patients with seasonal allergic rhinitis - SOYOĞUL GÜRER, ÜMRAN (ELSEVIER, 2005)
Immunotherapy plays an important role in the therapy of allergic rhinitis and bronchial asthma. However, there is not much information about the effects of allergen-specific immunotherapy (SIT) on the polymorphonuclear leukocyte functions. The aim of this study was to investigate the effects of specific immunotherapy on phagocytic and intracellular killing activities of polymorphonuclear leukocytes (PMN) derived from patients with seasonal allergic rhinitis. Twenty-four patients with seasonal allergic rhinitis documented to be sensitive to grass pollen were included in this study. Patients were divided into 3 groups. Group 1 (n = 7) received conventional immunotherapy whereas patients in Group 2 (n=7) were treated with short-term immunotherapy and the third group (n = 10) were given placebo during the study process. Both phagocytic and intracellular killing activities were significantly increased (p = 0.002, p < 0.0001, respectively) by conventional immunotherapy when compared to the first determination. In the short-term immunotherapy group, phagocytic activity was increased very significantly (p = 0.0001), whereas intracellular killing activity was not affected (p = 0.252). There were no changes in these parameters in the placebo group. These results suggest that allergen-specific immunotherapy has an enhancing effect on PMNs functions in the patients with seasonal allergic rhinitis. It should be clarified by further studies whether this enhancement might be considered as another beneficial effect of the immunotherapy. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: immunotherapy; pollen allergy; polymorphonuclear leukocytes; short-term and conventional immunotherapy; IMMUNOLOGICAL CHANGES; RESPONSES; CELLS; ANTIBODIES; TH2